Pengaruh Variasi Kuat Arus Pengelasan Terhadap Kekuatan Tarik dan Kekerasan Sambungan Las Plate Carbon Steel ASTM 36 - Adi Nugroho (Universitas Putera Batam, 2018)
This study aims to determine the effect of variations in the welding current to tensile strength and hardness welding SMAW with electrode E7016 on plate carbon steel ASTM A36 with a thickness 10 mm. large variations in use of welding current is 90 amps, 100 amps, 110 amps and 120 amps. This research was carried out by making spesiment test with the variation of welding current at 90 amperes, 100 amperes, 110 amperes and 120 amperes hereinafter spesiment test carried tensile testing and hardness to seek information influences that caused by the variation of welding current to the tensile strength and hardness of the welded joints. The results showed that the highest tensile strength (Ultimate Tensile Strength) were obtained on a sample of 110 amperes with value - average UTS at 467.78 MPa. While the highest hardness values obtained on a sample of 120 amperes with value - average in the region of 191 HV HAZ and in the region of 228 HV Weld metal.